日光照射とビタミンDの栄養について - 小林, 正 (衛生化学, 1985)
It is well known that the antirachitic activity of sunlight is due to the photochemical conversion of 7-dehydrocholesterol as provitamin D_3 to vitamin D_3 via previtamin D_3 in skin exposed to ultraviolet rays in sunlight (Dorno ray). On the other hand, it is documented that the major circulating metabolite of vitamin D in the plasma is 25-hydroxyvitamin D (25-OH-D) of which concentration directly reflects the repletion status of vitamin D nutrition. Therefore, we assayed the concentrations of 25-OH-D_2 and 25-OH-D_3 in the plasma samples obtained from about 1000 subjects including adults, mothers, infants and children. The mean and standard deviation of the assayed values of endogenous 25-OH-D_3 in the plasma of healthy adults was 23.0±10.1 ng/ml, which clearly showed the seasonal variation that the levels in summer were significantly higher than those in winter. On the other hand, the levels of mothers were about two times higher than the respective data of newborn infants and there was a highly significant correlation between mothers and newborns. On the basis of these data, the nutritional problems of vitamin D are discussed in this review.